Development of a Small Animal Ankle Arthrodesis Model. (January 2020) - Kadakia, Rishin J.; Devereaux, Emily J.; Ahn, Hyunhee; Traub, Brian C.; Kephart, Donald; Willett, Nick J.; Bariteau, Jason T.
Background: Our understanding of the biology of ankle arthrodesis is based largely on work in spine and long bone animal models. However, the local soft tissue and vascular anatomy of the foot and ankle is different from that of the spine. Accordingly, the objective of this study was to develop a small animal ankle arthrodesis model. Methods: A total of 12 Lewis rats successfully underwent ankle arthrodesis with stabilization consisting of a single Kirschner wire across the prepared tibiotalar joint. Based on high nonunion rates with this initial procedure, a modification was made consisting of a second pin crossing the joint. A total of 6 rats underwent the second procedure. Radiographs were taken postoperatively and in 2-week intervals up to 10 weeks. Micro computed tomography (µCT) and histological analysis was conducted at 10 weeks to assess the fusion mass. Osseous bridging of greater than 50% across the tibiotalar joint was deemed a successful fusion. Results: µCT analysis determined that 11 of the 12 rats in the single-pin cohort developed nonunions (8.3% fusion rate). In the dual-pin cohort, all 6 animals successfully fused (100% fusion rate). Histological analysis supported the radiographic imaging conclusions. Conclusion: While the initial procedure had a high nonunion rate, enhancing the stability of the fixation greatly increased the union rate. Clinical Relevance: The present work demonstrates the first reliable small animal ankle arthrodesis model. We believe that this model can be used in the development of novel therapies aimed at decreasing complications and increasing fusion rates.